Morphological characterization and agronomic evaluation of Lima bean (Phaseolus lunatus) accessions from the National Germplasm Collection of INIA, Ica, Peru (Bioagro, 2022)
Phaseolus lunatus is a leguminous of a great cultural importance in Peru, that has been domesticated by Nazca, Paracas and Mochica cultures. The great genetic variability obtained by those civilizations has not been completely identified yet.  The objective of this study was to characterize agro-morphologically nine accessions of this species comparing 17 qualitative and 12 quantitative parameters through descriptive analysis, ANOVA and Tukey’s test, correlation, principal components, and hierarchical clustering. The results indicated genetic variability. There was a positive and significant correlation between the main stem length and the average number of pods per plant, but a negative correlation with the average seed weight. Three groups of similar characteristics were identified based on their morphology and yield, where high values of pod and seed width, average number of pods per plant and average seed weight stood out. The promising accessions were 1ac, 2ac, 5ac, 8ac and 9ac.
Keywords: Genetic variability; grain legumes; hierarchical clustering; lima bean